ANALISIS PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN NO.1 TENTANG PENYAJIAN LAPORAN KEUANGAN PADA LAPORAN KEUANGAN PT. REKAYASA MINETECH INDONESIA (Minetech.id) - Kurniawan, Aceng; Fujianti, Nenden Asri (Journal of Information System, Applied, Management, Accounting and Research, 2025)
PT Rekayasa Minetech Indonesia (minetech.id) is engaged in mining training and consulting services. PSAK No.1 is an Indonesian financial accounting standard to regulate the presentation of financial statements. This study aims to improve financial statements in accordance with accounting standards, namely, Statement of Financial Accounting Standards No.1 (PSAK. No.1). This research was conducted using qualitative methods, In the financial statements of PT Rekayasa Minetech Indonesia presents two components of financial statements, namely the statement of financial position and income statement, while for the three components of the statement of changes in equity, cash flow statement, and statement of notes on financial statements PT Rekayasa Minetech Indonesia has not presented. PT Rekayasa Minetech Indonesia (minetech.id), has not fully followed the stages and preparations for the implementation of PSAK.The results of this study can be concluded as follows: (1) The company has not fully implemented PSAK No.1 in its financial statements (2) The implementation of PSAK No.1 on the statement of financial position and income statement is not in accordance with PSAK No.1 because it does not present accounts that should be presented in the financial statements in accordance with PSAK No.1.